Process intensification engineering for efficiency, sustainability and flexibility - Reay, D. A. (Elsevier/Butterworth-Heinemann, 2008)
Process intensification (PI) leads to a substantially smaller, cleaner, safer and more energy efficient process technology. For example, the scale reduction made possible by using high gravity fields to separate liquids has seen the reduction of distillation columns from 75m to a four of five metres in height in some areas. PI is a hot topic in chemical and process engineering - and beyond - and is now reaching a maturity that is seeing PI concepts applied to a wide range of processes and technologies. This is the first book to provide a practical working guide to understanding PI and developing successful PI solutions and applications. By demonstrating the broad application of PI this book will be of value to audiences looking to take current technologies into new process areas as well as those looking to further its use in the chemical engineering sector. As well as detailing technologies and practical applications the book focusses on safety, energy and environmental issues, giving guidance on how to incorporate PI in plant design and operation safely, efficiently and effectively. This book provides up to date access to the best current information on PI, both through the world-class experience of the authors and by pinpointing other significant sources of data, equipment and expertise. * Shows chemical and process engineers how to apply process intensification (PI) to their product, process or production line * A hard-working reference and user guide to the technology AND application of PI, covering fundamentals, industry applications, and supplemented my an development and implementation guide * Leading author team, including Professor Colin Ramshaw, developer of the HiGee high gravity distillation process at ICI, who is widely credited as the father of PI.
Keywords: Chemical process control.; Chemical processes -- Environmental aspects.; elektronické knihy; electronic books